Body composition is associated with changes in health-related quality of life in patients with knee and/or hip osteoarthritis - Jérémie Sellam; Francis Guillemin; Bernard Mazières; Anne-Christine Rat; Patrice Fardellone; Willy Ngueyon Sime (RMD Open)
Objective The objective of this study was to analyse the association between body composition and changes in health-related quality of life (HRQoL) of patients followed for hip and knee osteoarthritis (OA).Methods Longitudinal data from the Knee and Hip OsteoArthritis Long-term Assessments (KHOALA) cohort, a multicentre cohort of 878 patients with symptomatic knee and/or hip OA, were used. The main outcome criteria were changes in patient-reported outcomes measures, the Study Short Form-36 (physical functioning, pain, mental health and vitality) and the OsteoArthritis Knee and Hip Quality Of Life (OAKHQOL)(physical activity, pain and mental health). Body composition measurements were obtained from dual X-ray absorptiometry (DXA) scans in a subsample of 381 patients at year 3. Body composition variables were fat mass index (FMI (kg/m²)), percentage of fat mass, trunk to leg fat mass ratio (TFM/LFM) and skeletal muscle mass index (SMI (kg/m²)). To account for the correlation of repeated measures in each individual, GEE models were used.Results 290 patients with knee and 114 patients with hip OA were included in the analysis. In multivariate analysis, higher FMI at baseline and the presence of low lean mass were independently associated with worse physical functioning over time (β −0.02, 95% CI −0.03 to −0.01, p<0.0001 and β −0.21, 95% CI −0.02 to 0.02, p=0.02) for SF-36 dimensions. Higher TFM/LFM and SMI at baseline were associated with better mental health (β 0.09, 95% CI 0.02 to 0.15, p=0.008 and β 0.01, 95% CI 0.006 to 0.02, p<0.0001) and vitality. No association between body composition measures and pain remained in the multivariate analysis.Conclusions Higher FMI at baseline and the presence of low muscle mass were independently associated with worse physical function over 4 years, but not with pain. Higher TFM/LFM and SMI at baseline were associated with better mental health and vitality over time.